The Relationship Between Brainstem Structural Anatomical Parameters And Cognitive Function Impairment Based On The Indonesian Version Of Montreal Cognitive Assessment Score In Clinical Dementia Patients - Ivola Lita Widodo; Firman Parulian Sitanggang; I Made Dwijaputra Ayusta; I Wayan Gede Artawan Eka Putra (Green Publisher Indonesia, 2025)
Dementia is a neurodegenerative disorder characterized by a significant decline in cognitive function. Some studies suggest that structural changes in the brainstem can contribute to cognitive impairment. However, the relationship between the structural anatomical parameters of the brainstem and cognitive function impairment based on the Indonesian version of the Montreal Cognitive Assessment (MoCA) Score in patients with clinical dementia is still not widely studied. This study is an analytical observational study involving 65 patients with clinical dementia who underwent a head MRI examination at Ngoerah Hospital, Denpasar, Bali. The analyzed brainstem structural anatomical parameters included the diameter of the midbrain anteroposterior (AP), midbrain-to-pons ratio, superior cerebellar peduncle (SCP) width, middle cerebellar peduncle (MCP) width, and interpeduncular angle. The relationship between these parameters and cognitive function was measured using the MoCA-Ina score and analyzed by correlation and logistic regression tests. The average diameter of the AP midbrain was 11.1 cm (± 1.63 cm), the median midbrain-to-pons ratio was 0.19, and the median width of SCP and MCP was 1.8 cm and 7.9 cm, respectively. The results of the analysis showed that there was a sufficient positive relationship between the diameter of the AP midbrain and the midbrain-to-pons ratio (r = 0.329, p < 0.001) and between the width of SCP and MCP and the midbrain-to-pons ratio (r = 0.432 and 0.279, p < 0.001). The midbrain-to-pons ratio and MCP width were significantly related to the MoCA-Ina score (r = 0.265 and 0.447, p < 0.001).